2004
DOI: 10.1124/dmd.104.001198
|View full text |Cite
|
Sign up to set email alerts
|

Cyp2d6 Catalyzes 5-Hydroxylation of 1-(2-Pyrimidinyl)-Piperazine, an Active Metabolite of Several Psychoactive Drugs, in Human Liver Microsomes

Abstract: ABSTRACT:1-(2-Pyrimidinyl)-piperazine (1-PP) is an active metabolite of several psychoactive drugs including buspirone. 1-PP is also the major metabolite in the human circulation and in rat brains following oral administration of buspirone. This study was conducted to identify the enzyme responsible for the metabolic conversion of 1-PP to 5-hydroxy-1-(2-pyrimidinyl)-piperazine (HO-1-PP) in human liver microsomes (HLMs). The product HO-1-PP was quantified by a validated liquid chromatography-tandem mass spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…p-Hydroxy-PmP and its conjugates were identified in urine of man and animals given buspirone, indicating that PmP derived from the N-dealkylation of its parent drugs and other intermediates also undergoes oxidation and conjugation before excretion [70]. In contrast BITP is further oxidized at sulfur, with quantitative differences in the amounts of sulfoxide and sulfone derivatives excreted in man and rats given ziprasidone [31].…”
Section: Elimination Of 1-aryl-piperazinesmentioning
confidence: 99%
See 1 more Smart Citation
“…p-Hydroxy-PmP and its conjugates were identified in urine of man and animals given buspirone, indicating that PmP derived from the N-dealkylation of its parent drugs and other intermediates also undergoes oxidation and conjugation before excretion [70]. In contrast BITP is further oxidized at sulfur, with quantitative differences in the amounts of sulfoxide and sulfone derivatives excreted in man and rats given ziprasidone [31].…”
Section: Elimination Of 1-aryl-piperazinesmentioning
confidence: 99%
“…Correlation studies with isoform activities in human microsomes and metabolism by recombinant human CYP enzymes indicated that polymorphic CYP2D6 is responsible for the aromatic hydroxylation of mClPP [71], mCF 3 PP [72], and PmP [70]. This was supported by studies with CYP isoform-selective chemical inhibitors which showed that quinidine strongly reduced the formation rate of their hydroxylated derivative, from about 77% for mCF 3 PP to more than 95% for PmP in human liver microsomes and cDNA-expressed CYP2D6 or both [70][71][72].…”
Section: Elimination Of 1-aryl-piperazinesmentioning
confidence: 99%
“…Diese Methoden sind außergewöhnlich gut für die Anwendung an Pharmazeutika geeignet, da sie eine beeindruckende Toleranz gegenüber funktionellen Gruppen haben; einige Beispiele sind im Folgenden veranschaulicht. 2‐(Piperazin‐1‐yl)pyrimidin‐5‐ol ( 105 ) ist ein Metabolit von verschiedenen im Markt befindlichen Antidepressiva wie Buspiron ( 2 ), Tandospiron, Gepiron und Ipsapiron . Die Verbindung wird in vivo durch N‐Dealkylierung gebildet.…”
Section: Moderne C‐h‐oxidationenunclassified
“…[62] 1-(2-Pyrimidinyl)-piperazine is a major active metabolite of tandospirone, gepirone, ipsapirone, and buspirone which also have antidepressant/anxiolytic 5-HT 1A agonists′ activity. [63] The pharmaceutical importance of this nucleus is due to extensive occurrence in current marketed drug. [64] Various antidepressant drugs have a piperazine nucleus such as Amoxapine, Befuraline, Binospirone, Alnespirone, Buspirone, Flesinoxan, Gepirone, Ipsapirone, Nefazodone, Piberaline, and Tandospirone.…”
Section: Piperidinementioning
confidence: 99%